THE EFFECTIVENESS OF FACEBOOK WALL TO IMPROVE STUDENTS’ ABILITY IN WRITING RECOUNT TEXT: A Quasi Experimental Research - Risnawati HM; Nappu, Syamsiarna; Anugrawati, Nunung (FKIP Unismuh Makassar, 2018)
This research aimed in finding out the effectiveness of Facebook wall to improve students’ ability in writing recount text. The research applied Quasi experimental design model nonequivalent. The sample of the research were two class with the first class 20 and the second 20 class with using purposive sampling technique. The instrument of the research was writing English test. The population of the research was the eleventh grade student of SMA N 1 Sungguminasa and the number of sample was 20 students. The result of research in experimental class and control class in writing recount text in terms of content and mechanics in eleventh grade IPS 2 and IPS 3 showed. Percentage improving in experimental class in term content was 79.39 % improving from posttest 59.2, pretest 33, range pretest to posttest 26.2 % and 70.80 % improving in mechanics from posttest 69.6, pretest 40.75 range pretest and posttest 28.85 %. The percentage in control class in term of content was 66.31 % from posttest 54.05, pretest 32.5, range pretest to posttest 21.55 % and in mechanics was 58.28 % in posttest 60.7, pretest 38.35, range pretest to post test was 38.35%. Statistics hypothesis T-test value was 36.53 and T-table 1.78 which mean (H1) was significant improve.